Implementasi Keterlibatan Mahasiswa Dalam Analisis Mengenai Dampak Lingkungan Hidup Sebagai Perwujudan Kesadaran Lingkungan - Marlina Dea Nur Cahyanti; Rika Putri Handriyanti; Kris Yunianto; Anita Trisiana (RESEARCH FAIR UNISRI, 2020)
The analysts the impact of environmental the is a study on the impact of positive or negative of a project plans , used by the government to decide whether activities and projects were suitable environment .The purpose of the report is to ensure an activity and projects can run sustainable without damaging environment . Because with the amdal expected an activity and projects can use or manage natural resources effectively and efficient by means of maximize the impact of positive and minimize the impact of out the negatives . A huge amount of damage and environmental benefits when it is getting really bad for example , the damage to coral reefs , result of water pollution , air pollution as well as , are prone to air pollution caused by garbage during this complex. As some say it is also a form of human behaviour that is not satisfied and did not keep environment optimally. Progress is being made in the technology and discovery the odor of at the time of this covenant averse from its very for the survival of human life .All activities more is easy to do and is practically , but the utilization of the invention that unlocked drawn too much to the survey specifically in plastic that yet they created to accommodate an object the aga is easy to carry every where , and it will make hill corruption caused by monetary policies clean up the trash that the part of a car , and electronic . Since the 1950s plastic becomes an important part of in human life .Plastic used as raw materials for packaging , textile , bag, excelent of plastic that praktis , wanna , easy to find and also muah is facto sector-wide policy man surroundings chemicals that give rise to a complex problem .about emerge when disadai that plastic is not tedegadasi even though i was tependam inside the ground in a period of a very long time .From it then sevagai pollution response by the presence of a student to be garbage , students should be an example and reformer for the environment around .